Prognostic Value of Leucocyte Telomere Length in Acute Myocardial Infarction - Asri, Bin Said; Ho, Kian Hui; Jong, Siu Mei; Fong, Alan Yean Yip; Huang, Siaw San; Syed Hazran, Bin Syed Mohammad; Lee, James Zhi Yuan; Chew, Rebecca Su Li; Naemah, Binti Mazlan; Koh, Keng Tat; Shu, Francis Eng Pbeng; Tan, Chen Ting; et al. (Elsevier, 2018)
Introduction: Leucocyte telomere length (LTL) has been described as a marker of biological age, endothelial dysfunction and atherosclerosis. The association between LTL and clinical characteristics of Asian patients, and their outcomes following acute myocardial infarction (AMI) have been inconclusive. Objective: To investigate the relationship between LTL and developing AMI, the association of LTL with inpatient and 30-day mortality, and the comparison to LTL with established AMI risk scores in predicting these outcomes. Methodology: 100 patients aged 30-70 years admitted with an AMI to a tertiary referral center between May-Oct 2017 were enrolled; these were matched with 100 non-AMI ('healthy') controls for gender and age (+/- 1 year). Clinical data was obtained prospectively; inpatient and 30-day outcomes documented. LTL was reflected by a well described variable called a tis ratio (TSR). The TSR was measured at enrolment using a quantitative PCR-based methods (qPCR) and results blinded to the clinician.